APLIKASI FILTER PASIF PADA BEBAN INVERTER TIGA FASE BERBEBAN - Wahri Sunanda (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2014)
Harmonic is one of sinusoidal components, one wave period from which having multiple frequency of its fundamental frequency one, leading to electrical power quality problems. Harmonic distortion in term of voltage and current ones, generally is due to non linier impedance. Inverter is one of example of it. The result of the tests were showed that voltage harmonic distortion at inverter did not exceed the IEEE 519-1992 maximum limitation of 5%. While current harmonic distortion for each phase exceed 102,3%, 89,94% and 72,67%. After using passive filter, the total harmonic distortion (THD) current became 5,458 %, 6,118% and 5,968% for each phase.